Strategic sustainability orientation influence on organizational resilience: Moderating effect of firm size - Azra Ahmić (Business Systems Research (BSR), 2022)
Background: Owing to the heaviness of setbacks and shocks companies frequently face from the internal/external business environment, building solid organizational resilience and shifting towards strategic sustainability have become the top demands in today's wavering business world. Objectives: This study aimed to determine whether strategic sustainability orientation influences organizational resilience and how this relationship is moderated by firm size. Methods/Approach: This study uses a methodology structured around the stakeholder theory and embraces multiple regression analysis grounded on collected data from 124 enterprises in Bosnia and Herzegovina ambience. Results: Findings from the research revealed that strategic sustainability orientation significantly and positively influences organizational resilience and its three sub-components: anticipation, coping and adaptation capabilities. Results also uncovered that the Small size firms were significantly diverse from the Large and Medium size firms in terms of the influence of strategic sustainability orientation on three capabilities of organizational resilience. Conclusions: In addition to literature enriching in sustainability and organization by supplying empirical evidence of strategic sustainability orientation influence on organizational resilience, this study proposes and validates instruments for measuring strategic sustainability orientation and organizational resilience.
Keywords: Q01; M14; D81; H12; 330; organizational resilience; sustainability; strategic sustainability orientation; anticipation capabilities; adaptation capabilities